Dinasti Fatimiyah Di Mesir (909-1172): Kajian Pembentukan dan Perkembangannya (Jurnal Adabiya, 2020)
The discussion of the Fatimid Dynasty was an interesting discussion, because the controversy caused by the dynasty was enough to stir the Islamic world. Some author said this kingdom has a great contribution to introduce Muslims to science, because they build the University of al-Azhar. On the other hand, this kingdom is said to be an intolerant extremist kingdom, suppressing Sunni Muslims or Ahlussunnah wal Jamaah. The history of the kingdom filled with oppression, deceit, and deviation from the teachings of Islam is also another side that needs to be raised and discussed. Before discussing the political power of the Fatimid dynasty, we first discuss the ideology of this kingdom, because this is the underlying political movement. Fatimid dynasty was a Shiite-ideological kingdom, more precisely the Ismailis. Isma’ili Shi’ah is a Shi’ite sect who believes that Ismail bin Ja’far is the seventh priest, as for the majority of Shia (Shi’a Itsna Asyriyah) believes that Musah bin Ja’fa was the seventh imam after Ja’far ash-Sadiq. The differences in this subject matter then evolved into other doctrinal principles that increasingly distinguished Ismaili Shiite teachings from mainstream Shiite, Shiite Asna Asyriyah, so this teaching became a separate sect. Ismailis have beliefs that deviate far from the teachings and creeds of Islam. Like other Shiite sects, Isma’ilis Shiites also believe that priests are awake from sinful deeds, they are perfect figures, and there is no gap at all
Keywords: The Fatimid dynasty; university of al-Azhar; Syiah Ismailiyah